ANALISIS YURIDIS TERHADAP PRINSIP GOOD CORPORATE GOVERNANCE DALAM PENGELOLAAN PERSEROAN TERBATAS MENURUT UNDANG-UNDANG NOMOR 40 TAHUN 2007 - Suradiyanto Suradiyanto (Universitas Muhammadiyah Kalimantan Timur, 2017)
The purpose of this study was to determine and assess the implementation of the obligation to implement good corporate governance in the management of a limited liability company, the responsibility of directors to implement the oblig ation to implement good corporate governance in the management of a limited liability company, as well as the form of legal protection for minority shareholders related to the implementation of good corporate governance in the management limited liability company. This research is normative. Normative research focuses on the study of literature in order to obtain secondary data as the main data. Analysis of data used in this research is descriptive qualitative, ie data obtained from the study are presented descriptively and analyzed qualitatively. The results of this study stated that: (1) Application of the obligation to implement good corporate governance in the management of a limited liability company in Indonesia is still very low, it is mainly due to the fact that companies in Indonesia have not been fully has a Corporate Culture as the core of Corporate Governance. Understanding the open insight that we have not managed corporate correctly, or in other words, our corporate governance not run. Good corporate governance (GCG) is systems that regulate and control the company in order to create value added (value added) to all stakeholders. There are four main components needed the concept of Good Corporate Governance, namely fairness, transparency, accountability, and responsibility; (2) the Board of Directors as the party responsible for the management of the company has the obligation to apply the principles of good corporate governance principles requires the company. In carrying out these tasks, the directors must run it in good faith and full responsibility. Each member of the board of directors are personally liable for negligence in carrying out these tasks, and any losses suffered by the company or a third party to be borne by private property. Directors who do not carry out their responsibilities, in other words do not apply the principles of good corporate governance so losses in the company, according to the Company Law violating fiduciary duty; and (3) The form of legal protection for minority shareholders related to the implementation of good corporate governance in the management of a limited liability company, among others, with principles of justice in a publicly listed company requires the supreme authority to the AGM where a majority vote that will set the direction of the company, but to the minority shareholders should also be guaranteed fairness by giving him rights in accordance with the principles of good corporate governance.